OP0141 Ultrasound diagnostic and predictive value of interstitial lung disease in systemic sclerosis.diagnostic and predictive value of ultrasound in the assessment of interstitial lung disease. (12th June 2018) - Gutiérrez, J.; Gutierrez, M.; Almaguer, K.; Gonzalez, F.; Camargo, K.; Soto, C.; Bernal-Gonzalez, A.; Bertolazzi, C.; Clavijo-Cornejo, D.; Cruz-Arenas, E.; Pineda, C.; Gutierrez, M.
Abstract : Background: Interstitial lung disease (ILD) is a common complication of Systemic Sclerosis (SSc) and frequently may be cause of death of patients. High resolution computed tomography (HRCT) is the reference imaging tool for the assessment of ILD; however, its use may be limited for both ionising radiation and costs. In this way, pulmonary ultrasound (US) is revealing interesting potential in the assessment of ILD. Objectives: To determine the validity of pulmonary US in detecting subclinical ILD in SSc and to determine its predictive value for detecting disease progression. Methods: We included 133 SSc patients≥18 years-old without respiratory symptoms. Individuals with previous diagnosis of ILD or other pulmonary diseases were excluded. A rheumatologist performed the Borg scale dyspnea index, Rodnan skin score (RSS) and lung auscultation to confirm the subclinical respiratory status. Chest X-ray and respiratory function tests (RFT) were performed the same day in all patients. US was performed by a rheumatologist expert who was blinded to clinical assessment. To determine the concurrent validity HRCT was performed. Finally, serologic tests (anti-centromere, anti-Scl70) were obtained. HRCT findings were scored according to Warrick score, whereas US findings were classified according the previously proposed semiquantitative scale (0=normal, ≤5 B-lines; 1=slight, ≥6 and≤15 B-lines; 2=moderate, ≤16 and≥30 B-lines; 3=severe, ≥30 B-lines). In order to evaluate the inter-observer reliability, 50% of patients were assessed by 2 rheumatologists with different experience in US; both blinded to clinical data. A healthy control group matched for age and gender was included. A follow-up including US, RFT and Borg scale was done every 3 months until 12 months. Results: A total of 54 of 133 patients (40.6%) showed US signs of ILD in contrast to healthy controls (4.8%) (p=0.0001). The clinical and laboratory variables associated with ILD were: anti-centromere antibodies (p=0.005), Borg scale(p=0.004) and RSS(p=0.004). A positive correlation was demonstrated between the US and HRCT findings (p=0.001), confirmed also with the Chi square test (p=0.006). No association was shown with gender, age, disease duration, chest X-ray or RFT. Sensitivity and specificity of US in detecting ILD was 91.2% and 88.6% respectively. A Moderate inter-observer reliability of US findings was observed (kappa 0.50). In follow-up, a total of 30 patients (22.6%) that demonstrated ILD during first evaluation, showed US worsening in their ILD status. Interestingly, 9 of those 30 patients (30%) became symptomatic by the Borg scale. The elapsed time in which progression of ILD or clinical conditions was documented was between 6 and 9 months of follow-up. Conclusions: US showed a high prevalence of subclinical ILD in SSc patients. It demonstrated to be a valid, reliable and feasible tool to detect ILD in SSc and to follow-up its evolution. On the basis of our results we believe that US can be implemented as a screening tool for diagnosis of subclinical ILD in SSc. Disclosure of Interest: None declared